2018
DOI: 10.1007/s13197-017-3027-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcium and salicylic acid on quality retention in relation to antioxidative enzymes in radish stored under refrigerated conditions

Abstract: Effect of post harvest treatments with calcium chloride (CaCl) and salicylic acid (SA) on physiological and biochemical parameters in relation to activities of antioxidative enzymes were investigated in radish. Radish of variety Punjab Safed Mooli 2 was harvested, washed and treated with CaCl (1, 1.5 and 2%) or SA (1, 1.5 and 2 mM). Treated as well as untreated radish were placed in open trays and stored under refrigerated (5 ± 1 °C, 90% RH) conditions for 42 days. Treatment of radish with CaCl and SA slowed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Tareen et al [13] reported in peach that the treatment of SA could facilitate closure of stomata which inturn controls respiration and transpiration rate resulting in reduced weight loss. Similar findings were reported by [14][15][16]. Followed by salicylic acid , combined spray of salicylic acid and ascorbic acid @ 100 ppm was also perfomed well.…”
Section: Physiological Loss In Weight (%)supporting
confidence: 85%
“…Tareen et al [13] reported in peach that the treatment of SA could facilitate closure of stomata which inturn controls respiration and transpiration rate resulting in reduced weight loss. Similar findings were reported by [14][15][16]. Followed by salicylic acid , combined spray of salicylic acid and ascorbic acid @ 100 ppm was also perfomed well.…”
Section: Physiological Loss In Weight (%)supporting
confidence: 85%
“…JA functions as an upstream signal of the ICE-CBF pathway, positively modulating freezing responses [97]. JAZ1 and JAZ4 are JA signaling negative regulators interacting with ICE1 and ICE2 to repress their transcriptional activity [98]. Subsequently, they regulate the expression of CBF and other low-temperature responsive genes, thus affecting wheat cold resistance [97].…”
Section: Hormones and Ca 2+ Signalsmentioning
confidence: 99%
“…It is well known that SA plays a vital role in responding to abiotic stresses, apart from regulating crop growth, ripening and development [98,99]. SA activates the active oxygen species before low-temperature exposure; it promotes an increase in antioxidant enzyme activity and higher mRNA content of TaFeSOD, TaMnSOD, TaCAT gene transcripts, and free Proline after SCS [100].…”
Section: Hormones and Ca 2+ Signalsmentioning
confidence: 99%